Titik Singgung Penggabungan Gugatan dengan Gugatan Kelompok - Achmad Rizaldi, Fahim; Tobing, PL (UNES Law Review, 2023)
This research was conducted with the aim of finding out how to file a civil lawsuit, because the form and aspects of the lawsuit have the same characteristics. Aspects of the same form of lawsuit are cumulative lawsuits and group lawsuits. In this research method the author uses normative legal research, namely research carried out by analyzing applicable laws and regulations. Regarding the sources of legal materials used, they are divided into primary legal materials and secondary legal materials, where the primary legal materials are the main legal materials that are the basis for the study of this writing, namely statutory regulations. That there are differences in the forms of lawsuits even though they have some of the same characteristics, what makes them different is the accumulation of lawsuits / Combination of lawsuits regarding several legal issues that are both subjective and objective in nature, their use in civil courts which usually deal with issues of breach of contract, unlawful acts and divorce, etc. Meanwhile, group lawsuits are used for civil matters regarding consumer protection, the environment and forestry.